Building design at Arup. - Brensing, Christian (Detail engineering., 2013)
The idea of designing, planning and building as an inseparable process The idea of "Total Architecture", as described by Ove Arup in his vision of design, continues to serve as the maxim for the globally operating engineering firm ARUP and its Building Engineering Department. Drawing on selected projects from recent years, this second volume in the new DETAIL engineering series shows how future-oriented and sustainable civil engineering can be combined with this ideal of a holistic design process - always with the aim of achieving perfect unity of strength and elegance in every structure. The focus is placed on the different processes that have accompanied the presented construction projects. Connections are shown between the individual buildings whose synergies are pursued in an exemplary fashion.The remarkable building projects reveal what continues to drive and inspire the engineers at ARUP to this day: a passion for pioneering work. ARUP over the course of time Process descriptions from the perspective of the involved architects, engineers and planners From supporting structures to light design and building services to future-oriented civil engineering Interdisciplinary thinking, planning and realization "Total Architecture": comprehensive management of building projects, from the initial designs right through to construction.